The Influence of Harvesting Period on Lipid Associated Antioxidant Activity of Semicontinuously Grown Chlorella vulgaris - Chrismadha, Tjandara; Sartika, Diani; Setyaningsih, Iriani; Uju, Uju (ANNALES BOGORIENSES, 2010)
A green alga,Â  Chlorella vulgarisÂ  was grown semi-continuosly at various harvesting periods, and the lipid content and its associated antioxidant activity was examined. The harvesting periods were 9, 18, and 27 days, while the algal culture was placedÂ  in 10 L glassÂ  bottles provided with aerationÂ  for gas exchange andÂ  mixing. LightÂ  wasÂ  obtainedÂ  fromÂ  4ï´40Â  wattÂ  coolÂ  fluorescentÂ  lampsÂ  placedÂ  atÂ  oneÂ  sideÂ  ofÂ  theÂ  culture.Â  Room temperature wasÂ  26-32ï°C.Â  AlgalÂ  lipidÂ  extractionÂ  wasÂ  doneÂ  basedÂ  onÂ  liquidÂ  phaseÂ  separationÂ  of Â methanol :chloroform:waterÂ  andÂ  theÂ  antioxidantÂ  activityÂ  wasÂ  examinedÂ  byÂ  meansÂ  ofÂ  oxidationÂ  inhibitoryÂ  in ethanol emulsifiedÂ  limnoleicÂ  acid.Â  InÂ  addition,Â  aÂ  TLCÂ  analysisÂ  wasÂ  performedÂ  toÂ  identifyÂ  theÂ  antioxidant compouns solubleÂ  inÂ  theÂ  lipid.Â  TheÂ  resultsÂ  showedÂ  thatÂ  harvestingÂ  per iodÂ  hadÂ  aÂ  significantÂ  influenceÂ  onÂ  the algal lipidÂ  content,Â  whichÂ  wereÂ  11.94,Â  12.96,Â  andÂ  16.51%Â  ofÂ  theÂ  dryÂ  weightÂ  inÂ  theÂ  cultureÂ  withÂ  harvesting periods of 9, 18, and 27 days, respectively. No remarkable effect of theÂ  harvesting period on theÂ  antioxidant activity, which were observed to inhibit oxidation of linoleic acid up to 67-71%. There were five compounds found canÂ  be associated Â Â withÂ  theÂ  algalÂ  antioxidantÂ  activity,Â  whichÂ  wereÂ  pheophorbide -a,Â  chlorophyll-b,chlorophyll-a, phaeophytin-a, ï¢-carotene, and an unidentified one.Â Key words: microalgae, Chlorella vulgaris, lipid, antioxidant, harvesting periodÂ